Pengaruh Diskon Terhadap Kepuasan Konsumen UMKM Abyan Kosmetik Dan Aksesoris Di Kota Padang - Vivi Nila Sari; Shelbila Adita; Nila Sovianti; Sirotil Hasanah; Muhammad Ridho Alifa (Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to determine the effect of discounts on consumer satisfaction in MSMEs abyan cosmetics and accessories. Micro, Small and Medium Enterprises (MSMEs) are business activities that can expand employment, provide broad economic services to the community, play a role in the process of equitable distribution and increase community income, and increase economic growth, This important role has encouraged Padang City to continue to strive to improve the competitiveness of MSMEs in facing the community. The purpose of this study was to determine discount education on consumer satisfaction at MSMEs Abyan Cosmetics and Accessories. The compilation of this article was carried out by observation and interviews to collect data. The results of this study show that Abyan MSMEs can increase competitiveness.